2014
DOI: 10.3390/polym6092345
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Treatment on Tensile Properties of Low-Density Polyethylene/Cellulose Woven Biocomposites: A Preliminary Study

Abstract: Cellulose woven (CW) was surface treated by means of hexadecyltrimethylammonium bromide surfactant (HTAB) in aqueous solution medium at elevated temperature. The parameters of the surface treatment that have been studied are HTAB concentration (0.2, 0.4, 0.6, 0.8 and 1.0 wt%) and treatment time (1, 2, 3, 4 and 5 h). The untreated and treated CW filled low-density polyethylene (LDPE) biocomposites were prepared via compression molding technique. The tensile testing results of LDPE/CW biocomposites demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Therefore, surface treatments of the natural fibers by using chemicals have been proposed to overcome this problem [11,12]. However, there are some limitations of using chemicals, since they are expensive, and require more energy and time to carry out, and so forth [13]. In this preliminary investigation, 2 Journal of Composites a secondary filler such as a mineral has been used to evade the surface treatments of natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, surface treatments of the natural fibers by using chemicals have been proposed to overcome this problem [11,12]. However, there are some limitations of using chemicals, since they are expensive, and require more energy and time to carry out, and so forth [13]. In this preliminary investigation, 2 Journal of Composites a secondary filler such as a mineral has been used to evade the surface treatments of natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The crosshead speed was 5mm min 40mm gauge length [18]. The resultant biocomposites were conditioned in an oven at a temperature of 70°C for at least 24 hours prior to tensile test [20]. 24 samples from each composition were tested to determine the mean values, and the standard deviations were reported to show the error range [23].…”
Section: Tensile Test Of Biocompositesmentioning
confidence: 99%
“…Even though natural fibers could decrease the manufacturing cost of the biocomposite products, however, they have poor compatibility with synthetic polymer matrices, which can potentially deteriorate their mechanical and thermal properties. Hence, surface treatment of the natural fiber has been carried out to increase the compatibility of the biocomposites [20]. On the other hand, the utilization of secondary filler, for example, mineral particles in the biocomposites system also could improve their mechanical and thermal properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants have an amphiphilic character, owing to hydrophilic and hydrophobic functional groups [33,34]. Previous studies have indicated that the surfactants could act as interaction links between hydrophilic and hydrophobic polymers [35][36][37]. Furthermore, the presence of surfactants in polymer nanocomposites not only increased the uniformity of the nanofillers dispersion [8], but also improved the compatibility and wettability between polymer and nanofiller [11], as well as enhanced the final properties of the nanocomposites [18].…”
Section: Introductionmentioning
confidence: 99%